Pengaruh Media E-Book Cakap terhadap Keterampilan Intonasi Deklaratif dan Interogatif Siswa Kelas IV Sekolah Dasar - Misbahuddin Nur Fazri; Prana Dwija Iswara; Diah Gusrayani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
The limited availability of learning media specifically designed to train declarative and interrogative intonation remains a challenge in Indonesian language instruction at the elementary school level, although these suprasegmental features play an important role in determining the clarity of oral communication. Initial observations of fourth-grade students at a public elementary school in Sumedang Regency showed that the students tended to use flat intonation and were not yet able to distinguish between the intonation of statements and questions. This study aimed to analyze the effect of E-Book CAKAP as an interactive digital learning medium on fourth-grade students’ declarative and interrogative intonation skills. The study employed a quantitative approach using a quasi-experimental method and a nonequivalent control group design. The sample was selected through purposive sampling and involved 41 students, comprising 20 students in the experimental group and 21 students in the control group. Data were collected through performance tests in the form of paired interview conversations administered at the pretest and posttest stages and assessed using a validated rubric. The data were analyzed using the Mann–Whitney U test, N-Gain analysis, and Cohen’s d effect size. The results showed that the experimental group achieved a mean N-Gain of 0.51, categorized as moderate, which was higher than the control group’s mean of 0.36, categorized as low–moderate. The Mann–Whitney U test indicated a significant difference between the two groups (Z = −2.607; p = 0.009 < 0.05), with an effect size of 0.734, which was categorized as moderate and approaching large. These findings confirm that E-Book CAKAP, through its Probinton feature, pronunciation audio, colored lyrics, educational games, and voice-recording feature, effectively improves students’ declarative and interrogative intonation skills. This study contributes theoretically to the development of digital media for teaching speaking skills and practically provides guidance for educators in utilizing interactive e-books in Indonesian language instruction at the elementary school level. Future research should involve a larger sample and evaluate the long-term retention of intonation skills.